Perancangan Interior Pusat Informasi Peralatan Fisika di Surabaya - Garry Nathaniel Abet; Andereas Pandu Setiawan (Intra, 2014)
This design is aimed to educate the Surabaya’s people about equipment and physics knowledge. Remembering the general people’s circumscription about physics education. The design that I create is designing information centre as functional as possible. Physics equipment can help Surabaya’s people to increase their knowledge about physics education.